Female leadership, parental non-involvement, teenage pregnancy and poverty impact on underperformance of learners in the further education and training - Potgieter, Cheryl (HTS teologiese studies, 2019)
A number of studies have explored the underperformance of learners. However, there is a paucity of research in South Africa, which focuses primarily on how school leadership, commonly referred to as school management teams (SMTs), accounts for the underperformance of learners and thus the underperformance of schools. To fill this gap, the current study, undertaken in two schools in a district in KwaZulu-Natal province, aimed to explore through a qualitative approach the opinions of SMTs regarding underperformance in the further education and training (FET) phase. School management teams were interviewed using a semi-structured interview guide and in-depth face-to-face interviews. The interview guideline had a set of broad flexibly worded questions that allowed for in-depth discussion. Data were analysed using a thematic data analysis method. The school management team accounted for, and linked underperformance to a range of reasons. In this article, we present findings which emerged in relation to leadership weaknesses, particularly female leadership weaknesses, socio-economic challenges such as child-headed households and its consequences, teenage pregnancy, violence experienced by female learners, health of learners and educators and poverty. Systemic and structural societal challenges were flagged in the interviews as also impacting on the overall cognitive and psycho social development of learners. School management teams addressed the challenges by implementing a number of interventions that they reported were not successful. There is no simple answer to address the problem and we argue for a social compact which is inclusive of all stakeholders and suggest that intervening at the local level may not have a nation-wide impact but it would have an impact on a particular school. Sensitivity training, which includes gender sensitivity training, and leadership training and support is suggested as part of the interventions. Certain best practices could then be shared with other schools which face similar challenges.